Preexisting coronary artery disease among coronavirus disease 2019 patients: a systematic review and meta-analysis. Issue 8 (August 2022) - Zuin, Marco; Rigatelli, Gianluca; Bilato, Claudio; Rigatelli, Alberto; Roncon, Loris; Ribichini, Flavio
Abstract : Aims: The prevalence and prognostic implications of coronary artery disease (CAD) in patients infected by the novel coronavirus 2019 (COVID-19) disease remain unclear. Methods: We conducted a systematic review and meta-analysis to investigate the prevalence and mortality risk in COVID-19 patients with preexisting CAD. We searched Medline and Scopus to locate all articles published up to December 8, 2021, reporting data of COVID-19 survivors and nonsurvivors with preexisting CAD. Data were pooled using the Mantel-Haenszel random effects models with odds ratio (OR) as the effect measure with the related 95% confidence interval (CI). Results: Thirty-eight studies including 27 435 patients (mean age 61.5 and 70.9 years) were analysed. The pooled prevalence of preexisting CAD was 12.6% (95% CI: 11.2–16.5%, I 2 : 95.6%), and resulted as higher in intensive care unit patients (17.5%, 95% CI: 11.9–25.1, I 2 : 88.4%) and in European cohorts (13.1%, 95% CI: 7.8–21.6%, P  < 0.001, I 2 : 98.4%). COVID-19 patients with preexisting CAD had a two-fold risk of short-term mortality (OR 2.61, 95% CI 2.10–3.24, P  < 0.001, I 2  = 73.6%); this risk was higher among Asian cohorts (OR: 2.66, 95% CI: 1.79–3.90, P  < 0.001, I 2 : 77.3%) compared with European (OR: 2.44, 95% CI: 1.90–3.14, P  < 0.001, I 2 : 56.9%) and American (OR: 1.86, 95% CI: 1.41–2.44, P  < 0.001, I 2 : 0%) populations. The association between CAD and poor short-term prognosis was influenced by age, prevalence of hypertension (HT), DM and CKD. Conclusions: Preexisting CAD is present in approximately 1 in 10 patients hospitalized for COVID-19 and significantly associated with an increased risk of short-term mortality, which is influenced by age, HT, DM and CKD.